Apolipoprotein A1-Related Proteins and Reverse Cholesterol Transport in Antiatherosclerosis Therapy: Recent Progress and Future Perspectives - Xiuting Xu; Zikai Song; Bao Mao; Guoliang Xu (Hindawi-Wiley, 2022)
Hyperlipidemia characterized by abnormal deposition of cholesterol in arteries can cause atherosclerosis and coronary artery occlusion, leading to atherosclerotic coronary heart disease. The body prevents atherosclerosis by reverse cholesterol transport to mobilize and excrete cholesterol and other lipids. Apolipoprotein A1, the major component of high-density lipoprotein, plays a key role in reverse cholesterol transport. Here, we reviewed the role of apolipoprotein A1-targeting molecules in antiatherosclerosis therapy, in particular ATP-binding cassette transporter A1, lecithin-cholesterol acyltransferase, and scavenger receptor class B type 1.